HBI transcription factor-mediated ROS homeostasis regulates nitrate signal transduction. Issue 9 (15th June 2021) - Chu, Xiaoqian; Wang, Jia-Gang; Li, Mingzhe; Zhang, Shujuan; Gao, Yangyang; Fan, Min; Han, Chao; Xiang, Fengning; Li, Genying; Wang, Yong; Yu, Xiang; Xiang, Cheng-Bin; et al.
Abstract: Nitrate is both an important nutrient and a critical signaling molecule that regulates plant metabolism, growth, and development. Although several components of the nitrate signaling pathway have been identified, the molecular mechanism of nitrate signaling remains unclear. Here, we showed that the growth-related transcription factors HOMOLOG OF BRASSINOSTEROID ENHANCED EXPRESSION2 INTERACTING WITH IBH1 (HBI1) and its three closest homologs (HBIs) positively regulate nitrate signaling in Arabidopsis thaliana . HBI1 is rapidly induced by nitrate through NLP6 and NLP7, which are master regulators of nitrate signaling. Mutations in HBIs result in the reduced effects of nitrate on plant growth and ∼22% nitrate-responsive genes no longer to be regulated by nitrate. HBIs increase the expression levels of a set of antioxidant genes to reduce the accumulation of reactive oxygen species (ROS) in plants. Nitrate treatment induces the nuclear localization of NLP7, whereas such promoting effects of nitrate are significantly impaired in the hbi-q and cat2 cat3 mutants, which accumulate high levels of H2 O2 . These results demonstrate that HBI-mediated ROS homeostasis regulates nitrate signal transduction through modulating the nucleocytoplasmic shuttling of NLP7. Overall, our findings reveal that nitrate treatment reduces the accumulation of H2 O2, and H2 O2 inhibits nitrate signaling, thereby forming a feedback regulatory loop to regulate plant growth and development. Abstract : Transcriptional regulation of ROS by HBI family proteins contributes to nitrate signal transduction through regulating the nucleocytoplasmic shuttling of NLP7.